Proses Internalisasi Nilai-nilai Karakter pada Pembelajaran Matematika di MAN Insan Cendekia Jambi dalam Konteks Kurikulum 2013: The Process of Internalizing Character Values in Mathematics Learning at MAN Insan Cendikia in the 2013 Curriculum Context - Ahmad Puguh Eriawan; Syamsurizal Syamsurizal; Kamid Kamid (Universitas Jambi, 2017)
KTSP curriculum changed into the 2013 curriculum making the assessment of students no longer only focus on cognitive aspects, but also focused on the process of character building during the learning process. This study aims to describe the process of internalizing character values ​​in mathematics learning at MAN Insan Cendekia school in Jambi in the context of the 2013 curriculum. Descriptive qualitative research methods is employed to describe the internalization process through the provision of questionnaire instruments with closed questions, observation in the mathematics learning process, and in-depth interviews. The internalization process of character values in each study is a significant way of shaping the character of each student, strengthening the 2013 curriculum which emphasizes soft skills is a guideline that must be done by each teacher in the learning process in the classroom. The results of the study explained that the subject of the study carried out an internalization process of character values by accepting and carrying out the tasks given by the teacher with the basics of philosophical understanding that was used during the learning process of mathematics.